2017
DOI: 10.1371/journal.ppat.1006721
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of HSV genome nuclear entry and compaction state transitions using bioorthogonal chemistry and super-resolution microscopy

Abstract: We investigated the spatiotemporal dynamics of HSV genome transport during the initiation of infection using viruses containing bioorthogonal traceable precursors incorporated into their genomes (HSVEdC). In vitro assays revealed a structural alteration in the capsid induced upon HSVEdC binding to solid supports that allowed coupling to external capture agents and demonstrated that the vast majority of individual virions contained bioorthogonally-tagged genomes. Using HSVEdC in vivo we reveal novel aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 79 publications
5
77
0
Order By: Relevance
“…Therefore, we developed a quantitative evaluation of the RC overlapping areas in each cell. We found that common pixel based co-localization methods do not provide an accurate estimate of the degree of overlap between HSV-1 RCs, probably due to the relaxed form of the replicating viral DNA (34). Our results following infection with one virus carrying the two tag sequences (OK31) showed limited co-localization at the pixel level, similar to results obtained by two probes corresponding to adjacent loci on HSV-1 genomes (53).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Therefore, we developed a quantitative evaluation of the RC overlapping areas in each cell. We found that common pixel based co-localization methods do not provide an accurate estimate of the degree of overlap between HSV-1 RCs, probably due to the relaxed form of the replicating viral DNA (34). Our results following infection with one virus carrying the two tag sequences (OK31) showed limited co-localization at the pixel level, similar to results obtained by two probes corresponding to adjacent loci on HSV-1 genomes (53).…”
Section: Resultsmentioning
confidence: 90%
“…Second, the smaller RC could interact with two larger RCs that flank both sides of the small RC and eventually unite into a single larger RC. A third mechanism could involve the recently observed condensed viral genomes at the edge of RCs (34). Sekine et al showed that at 3HPI several incoming genomes remain condensed at the periphery of an enlarging RC (34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations